Identifikasi Potensi Bahaya untuk Meminimalkan Kecelakaan Kerja dengan Metode Hazard and Operability Study (HAZOP) di PT SEGARA - Muhammad Rais Budiman; Agustian Suseno; Wahyudin Wahyudin (Peneliti.net, 2022)
Abstract: At this time, the development of the industry is so rapid, which results in its business processes involving many sophisticated machines and equipment. As a result of these developments increase the risk of accidents at work. The purpose of this study is to identify potential hazards and provide suggestions in an effort to prevent work accidents. This research is a qualitative research with primary data obtained from field observations and secondary data in the form of literature searches. The analysis was carried out using the Hazard and Operability Study (HAZOP) method. The research results obtained are work accidents that occur at PT. SEGARA is caused by the worker's carelessness when using the machine so that workers can get injured and lose their limbs as a result of being hit by the machine. Types of accidents that often occur at PT. SEGARA eye irritation due to welding, as well as defects due to exposure to machines. The solution in preventing a work accident that occurred at PT. SEGARA is to use the right PPE and continue to improve knowledge of work safety.. Keyword: Accident, Hazard, HAZOP.